Peran Notaris Dalam Membuat Akta Wasiat Yang Bertentangan Dengan Kompilasi Hukum Islam (Studi Akta Notaris Nomor 12 Tanggal 27 Oktober 1984 Tentang Wasiat) - Mohammad Hafid Arkan (Universitas Islam Indonesia, 2020)
This study aims to analyze whether the notary in making deeds must always fulfill the wishes of the client, then analyze the role of the notary in making will deeds based on the provisions of the applicable laws and regulations in Indonesia, and the legal consequences of wills made by notaries who contrary to the prevailing legal system (study of Notary deed No. 12 dated 27 October 1984 on Will). This is an empirical juridical research. The results of the research explain that there is no obligation for the notary to fulfill every wish of the client without first ensuring that the formal and material requirements can be fulfilled by the client, then the role of the notary in making a will before a notary refers to the provisions of Article 1 paragraph (1) of UUJN, and the legal consequence of an authentic will deed made by a Notary who commits an act against the law for his negligence in the deed creation loses the deed's authenticity and becomes a deed under-hand and the authentic deed can be canceled if the arguing party can prove it in court proceedings.